Pengaruh Bauran Pemasaran Terhadap Minat Berkunjung ke Coban Lanang Kota Batu - Irawan, Muhammad Iqra; Rahmadian, Aprillia; Puspawigati, Ani (Jurnal Pariwisata Tourista, 2023)
Coban Lanang is now one of the tourist destinations in Batu City. The concept of semi-modern natural tourism is seen in the spatial layout, facilities, and tourist products that attract the attention of tourists. On August 8, 2021, Coban Lanang Tourism was opened in stages. This research focuses on the implementation of the 4P marketing mix strategy (products, prices, promotions, and places) in Coban Lanang tourist destinations. Using quantitative research methods with a total of 50 respondents. Place is the dominant variable that influences a person's interest in visiting Coban Lanang tourist destinations.